"I Know the Assumptions From?" ? About Creating Teachers? Opinions On the Transformations of Special-Need Education - Gajdzica, Zenon (INSTED: Interdisciplinary Studies in Education & Society, 2011)
The next stage of reforming the education of pupils with special needs, being introduced in 2011, is carried out with no big emotions and it does not polarize the positions of reformers and opponents as it happened with reforms in the past. Is it an optimal change or maybe unconditionally necessary? Or, perhaps, are there any other premises of such a status quo? How is the reform perceived by its practical executors ? teachers and will they be their moral agents? In the study I focus on one aspect of the above-expressed doubts. It covers characteristic features and seeking the conditions of the opinions of primary and lowersecondary school teachers about the reform. Since the discussed reform does not belong to spectacular transformations of the system of native education I start from a short introduction in order to at least superficially illustrate the undergoing changes. In the second part of the text I consider possible ways of creating teachers? attitudes towards the implemented reform referring them to the sources of colloquial, scientific and institutional knowledge.